Update on the Discovery of Efflux Pump Inhibitors against Critical Priority Gram-Negative Bacteria - Nina Compagne; Anais Vieira Da Cruz; Reinke T. Müller; Ruben C. Hartkoorn; Marion Flipo; Klaas M. Pos (MDPI AG, 2023)
Antimicrobial resistance (AMR) has become a major problem in public health leading to an estimated 4.95 million deaths in 2019. The selective pressure caused by the massive and repeated use of antibiotics has led to bacterial strains that are partially or even entirely resistant to known antibiotics. AMR is caused by several mechanisms, among which the (over)expression of multidrug efflux pumps plays a central role. Multidrug efflux pumps are transmembrane transporters, naturally expressed by Gram-negative bacteria, able to extrude and confer resistance to several classes of antibiotics. Targeting them would be an effective way to revive various options for treatment. Many efflux pump inhibitors (EPIs) have been described in the literature; however, none of them have entered clinical trials to date. This review presents eight families of EPIs active against Escherichia coli or Pseudomonas aeruginosa. Structure-activity relationships, chemical synthesis, in vitro and in vivo activities, and pharmacological properties are reported. Their binding sites and their mechanisms of action are also analyzed comparatively.